Bending Assessment and On-body Investigation of a Textile Antenna for Body-Centric Wireless Communication Applications - Sandeep, D Ram; Khan, Habibulla; Madhav, B T P; Gayathri, M; Priyatham, A Kalyana; Nikhilvarma, M; Kumar, S Chandra Sekhar; Salma, S (IOP conference series. Materials Science and Engineering, 2022)
This article presents the design and investigation of a textile-based antenna for body wireless communication applications. The Christmas tree structure inspired the antenna design, and a staircase-like defective ground element supported it. The antenna is tiny with a footprint of 30×20×1 mm 3 and is developed on polyester fabric. This material has good grades of flexibility and has the most negligible affinity to moisture, so it was chosen as a suitable substrate for the developed wearable antenna. The radiating elements and grounds conductivity is actualised using the adhesive conductive copper tape. The propounded antenna operates in a treble band of Telemetry, Industrial Scientific and Medical (ISM), and X-band at 4.5, 5.8, and 8 GHz frequencies. The developed textile antenna is intended for body applications, so it was methodically examined by bending it at various vertical and horizontal bending angles. This analysis shows that the antenna’s resonating frequencies are not substantially varied in the vertical and horizontal bending aspects. The antennas on body performance were also examined by placing the prototype directly on the subject’s skin. These results confirm the developed antennas’ applicability for body wireless communication applications.